SOME CONCEPTS ON LAW IN WESTERN PHILOSOPHY IN THE PRE-MODERN PERIOD - Ngo Minh Thuong, (IJRDO- Journal of Educational Research, 2020)
Apart from the achievements and outcomes, the reality of building a socialist rule-of-law state in Vietnam today also reveals many inadequacies and limitations. One of them is the theoretical lack of building a rule-of-law state, as well as the confusion in practical activities. Therefore, it is essential to study the concepts of law in Western philosophy in the pre-modern period. With that in mind, by using the system of research methods of material dialectic, this article mainly clarifies some basic issues in the concept of pre-modern law, such as the origin, the role and the nature of the law with the recognition, respect and protection of human rights; and the law is an expression of a common will.